Effect of cadmium ions on lipid peroxidation and activities of antioxidant enzymes of growing wheat (Triticum aestivum L.) shoots - Zh. H. Mukhaelyan; G. H. Poghosyan; P. H. Vardevanyan (ՀՀ ԳԱԱ հրատ.)
The investigation of the effect of CdCl2 different concentrations (20, 50, and 100 mM Cd) on growth of germs of winter wheat (Triticum aestivum L.) has been carried out for 12 days. The influence of Cd2+ ions on lipid peroxidation and antioxidant system function of wheat shoots cells has been also studied. It has been shown that increasing Cd supply decreased shoots growth (fresh weight) and induced oxidative stress as was indicated by the enhancement of lipid peroxidation rate (MDA-level). Activities of antioxidant enzymes –catalase (CAT) and guiacol peroxidase (GPX) also have been changed under Cd-stress; CAT activity was less affected and even lowered, in case when GPX activity was markedly increased. The role of plant age on formation of biosystem reaction was also discussed in present work. The very high peroxidase activity in wheat shoots, probably may be an important part of Cd-resistance machinery of wheat. The obtained results indicated that Cd-tolerance of wheat may be related with the activation of the antioxidant system to avoiding the toxicity of heavy metal.Ուսումնասիրվել է CdCl2 տարբեր կոնցենտրրացիաների (20, 50, և 100 մկՄ Cd) ազդեցությունը ցորենի (Triticum aestivum L.) ծիլերի աճի, դրանցում լիպիդների պերօքսիդային օքսիդացման և հակաօքսիդանտային ֆերմենտների ակտիվության վրա: Ցույց է տրվել, որ Cd2+ առկայությամբ աճեցված բույսերի ծիլերի զանգվածը նվազում է, և աճում է լիպիդների պերօքսիդացման վերջնական արգասիքներից մեկի` մալոնային երկալդեհիդի (ՄԵԱ) քանակը: Cd2+-ինդուկցված սթրեսը արտահայտվում է նաև կատալազի ակտիվության նվազմամբ և պերօքսիդազի ակտիվության նշանակալի աճով: Քննարկվում է բույսի տարիքային գործոնի հնարավոր դերը կենսահամակարգի պատասխան ռեակցիայի ձևավորման մեջ: Պերօքսիդազի ակտիվության աճը` ի պատասխան ծանր մետաղի ազդեցության, հավանաբար, վերջինիս նկատմամբ բույսի դիմադրության (Cd-ռեզիստենտության) մեխանիզմի կարևոր բաղադրիչը կարող է հանդիսանալ:Изучено влияние разных концентраций CdCl2 (20, 50, и 100 мкМ) на рост, интенсивность процессов перекисного окисления липидов и функционирование антиоксидантной системы проростков пшеницы (Triticum aestivum L.). Установлено, что использованные концентрации кадмия ингибируют увеличение биомассы проростков, а также приводят к накоплению малонового диальдегида (МДА) в них. При этом активность каталазы в проростках в присутствии кадмия снижается, а активность пероксидазы значительно возрастает. Обсуждается вопрос возможной возрастной зависимости ответной реакции растения на воздействие ионов тяжелого металла. Высокая пероксидазная активность, вероятно, может быть частью механизма Cd-толерантности пшеницы.
Keywords: Biology; Biochemistry